Vandalism as a tool for Ukrainian politics of memory of Soviet monumental heritage (2009-2015) - Liubarets, A. (Український історичний збірник, 2017)
The study is an analysis of vandalism (unauthorized destruction or damage) of Soviet monuments as a form politics of memory by Ukrainian influential agents of memory during the greatest prevalence of such actions (2009-2015). We will try to describe the role of the mass Ukrainian political forces and officials in both support of unauthorized demolition and damaging of Soviet monuments and its protection and recovery (because a resistance to vandalism is also a form of memory politics). The article will show linkages between sponteneaus initiantives of monuments demolitions and memory politics of major Ukrainian memory agents.